Bridging the Gap: Addressing Skills Mismatch Among Librarians - Toszewska-Czerniej, Weronika (Zbliżanie rozbieżności: niwelowanie niedopasowania umiejętności zawodowych bibliotekarzy, 2025)
Aim: In the coming years most local libraries will undergo a fundamental transformation, mainly due to the changing nature of content. As access to data and information is changing to digital and online formats, the need for physical materials is decreasing, which allows libraries to focus less on their basic activities, including storing collections of diverse publications, and more on building user experience. The main objective of this paper was to present the results of measuring selected areas of skill mismatch among librarians from the West Pomeranian (zachodniopomorskie) voivodeship in Poland. Methodology: The increasing digitalisation of library services requires librarians to adapt their skill sets to modern challenges. This study examined the extent of skill mismatches among librarians in the West Pomeranian voivodeship. Using a computer-assisted web interview (CAWI) methodology, data were collected from 80 librarians to assess the alignment of their qualifications with the job requirements. Results: The findings indicate that interpersonal skills were the least well-matched, whereas digital skills were relatively well-aligned with job expectations. Contrary to assumptions, most librarians do not perceive themselves as overqualified. These results suggest that future training should focus primarily on improving librarians' interpersonal competencies, particularly in online user interactions. The study highlights the need for continuous professional development and skill adaptation to enhance library services in the digital era. Implications and recommendations: Contrary to common perceptions, most librarians do not feel overqualified, indicating a good overall match between education and work requirements. It is recommended that training programs and curricula place greater emphasis on interpersonal and user-experience skills. Continuous professional development and the use of competency frameworks can help guide these improvements. Tailored, regional training and ongoing monitoring of skill mismatches are also essential for enhancing library services in the digital age. Future research should explore how librarians’ skill mismatches have evolved over time, especially in response to ongoing digital transformation. Comparative and generational studies could reveal regional differences and age-related trends in adapting to new competencies. Additionally, examining user perceptions and the effectiveness of training programmes would provide valuable insights into improving library services and staff development. Value: Mismatches of specific skill groups for librarians were determined and categorised based on the guidelines of the American Library Association. The analysis of the results showed the weakest and the best matched skills. The conducted study also included an analysis of the levels of matching of the digital skills related to the work of librarians, showing the level of skill diversity for this group. The article identified horizontal and vertical mismatches of librarians' skills, which showed a generally good level of matching both the profile and the level of education of this professional group. The determination of the levels of mismatching was made by verifying the adopted hypotheses. Based on the verification of the adopted hypotheses, recommendations were made regarding actions that would improve the levels of skill matching.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 119-133
Keywords: human capital; skills; librarianship; skills mismath; kapitał ludzki; umiejętności; bibliotekarstwo; niedopasowanie umiejętności